RELATED KNOWLEDGE AND ATTITUDE OF THE USE OF ANTIBIOTICS IN PATIENTS WITH DIARRHEA IN KENDARI INDONESIA - Langgesa, Alfrida Alik; Tosepu, Ramadhan; Lestari, Hariati; Effendy, Devi Savitri; Ali Imran, La Ode; Asfian, Pitrah; Bahar, Hartati; Sakka, Ambo (YCAB Publisher & IAKMI SULTRA, 2015)
Backgrounds: The use of antibiotics to be a problem in the handling of patients with diarrhea in the city of Kendari. The negative impact of the use of antibiotics is the emergence and development of bacteria resistant to antibiotics, the emergence of diseases caused by bacterial superinfection, the occurrence of side effects of drugsObjective: To determine the relationship between knowledge and attitude of people with diarrhea in the city kendariMethods: This research was analytic observational cross-sectional method with the entire patient population is diarrhea who came to visit in as many as 234 people Poasia Health Center and the study sample is equal to 148 people. The sampling technique is done by random sampling techniqueResults: The results of the analysis indicate knowledge Î± (0.05)> Ï (0,000) or the chi-square value> value table that is 29.658> 3.841, then HO is rejected and H1 is accepted. While the attitude showed Î± (0.05)> Ï (0,000) or the chi-square value> value table that is 52.269> 3.841, then HO is rejected and H1 acceptedConclusions: There is a relationship between knowledge and attitudes to the use of antibiotics in patients with diarrhea in Kendari. A person who has enough knowledge about the use of antibiotics in patients with diarrhea then it will not use antibiotics unless the prescribing physician.